STUDI DESKRIPTIF TINGKAT PENGETAHUAN KADER PASCA PELATIHAN PEMBERIAN MAKAN BAYI DAN ANAK (PMBA) DI KECAMATAN KALASAN KABUPATEN SLEMAN - Ajeng Ersyam Putri; Prastiwi Putri Basuki; Yuli Ernawati (Jurnal Delima Harapan, 2021)
Background: One of the efforts to improve community nutrition is through PMBA training for cadres. In the implementation, training has been carried out in several generations in the Kalasan sub-district, but there is no evaluation data on the level of knowledge about Infant and Young Child Feeding (IYCF) to cadres. Objective: To know the description of cadres' knowledge level on the Infant and Young Child Feeding in Kalasan District. Method: This study used a quantitative descriptive method. The sampling technique used was purposive sampling by involving 52 Posyandu cadres in Kalasan District. Results: The results showed that 33 people (63.5%) are in the good category, 18 people (34.6%) are in the moderate category and 1 person (1.9%) is in the poor category. Most of the cadres who already knew the definition of IMD is 51 (98.1%) people but had a lack of understanding about the implementation of IMD at surgical birth (36.5%), a sign of good attachment during breastfeeding (17.3%), and about snacks in infants 6-9 months (44.2%). Conclusion: The distribution results on the knowledge levels of infant and child feeding are mostly good, especially in understanding the definition of IMD, although there is a lack of knowledge on understanding the implementation of IMD in operative births, about signs of attachment during breastfeeding, and about complementary foods.